2016
DOI: 10.4067/s0718-52862016000200001
|View full text |Cite
|
Sign up to set email alerts
|

Predicción del fracaso empresarial: Una contribución a la síntesis de una teoría mediante el análisis comparativo de distintas técnicas de predicción

Abstract: Predicción del fracaso empresarial. Una contribución a la síntesis de una teoría mediante el análisis comparativo de distintas técnicas de predicción*1 Business failure prediction. A contribution to the synthesis of a theory, through comparative analysis of different prediction techniques

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…He concluded that an artificial neural network was the most recommended technique for the Korean hotel sector due to its high accuracy and small relative error costs. de Llano Monelos et al. (2016) compared the effectiveness of eight popular prediction methods, pointing out that different methodologies used in each study did not show significant influence on the results, and they suggested focusing on improving the quality of informational context of variables rather than designing sophisticated analysis techniques.…”
Section: Literature Review Of Bibliometric Study and Bankruptcy Predimentioning
confidence: 99%
“…He concluded that an artificial neural network was the most recommended technique for the Korean hotel sector due to its high accuracy and small relative error costs. de Llano Monelos et al. (2016) compared the effectiveness of eight popular prediction methods, pointing out that different methodologies used in each study did not show significant influence on the results, and they suggested focusing on improving the quality of informational context of variables rather than designing sophisticated analysis techniques.…”
Section: Literature Review Of Bibliometric Study and Bankruptcy Predimentioning
confidence: 99%
“…In 1966, the first research paper on business failure was published in the Journal of Accounting Research [22]. Since then, a great deal of research has focused on predicting corporate insolvency scenarios; therefore, it is necessary to evaluate the development of this research and identify the main actors (e.g., countries, institutions, authors) and suggest directions for future research [23][24][25][26][27]. A review of articles related to the subject is of great help to those who wish to approach this line of research, since the literature often appears confusing and chaotic for those who start in this field [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%